Microstructure evolution of Au/SnSb-CuNiAg/(Au)Ni during high temperature aging. Issue 2 (3rd October 2019) - Han, Bangyao; Sun, Fenglian; Li, Tianhui; Liu, Yang
Abstract : Purpose: The purpose of this paper is to investigate the morphology evolution and the composition transformation of Au-Sn intermetallic compounds (IMCs) of the new Au/Sn-5Sb-1Cu-0.1Ni-0.1Ag/(Au)Ni solder joint during the high temperature aging. Design/methodology/approach: Sn-5Sb-1Cu-0.1Ni-0.1Ag solder balls (500 µm in diameter), heat sink with structure of 7.4 µm Au layer on 5 µm Ni-plated Cu alloy and Si chip with 5.16 µm plated Au were used to fabricate micro-solder joints. The joints were performed in a furnace at 150°C for 150, 250 and 350 h aging. The samples were polished and deep etched before analyzed by metallographic microscope and scanning electron microscopy, respectively. Energy dispersive x-ray spectroscopy was used to identify the composition of the IMCs. Findings: ß -(Au, Ni, Cu)10 Sn phase is formed during the soldering process. The IMCs evolution has two periods during the aging. The first is the ξ -(Au, Ni, Cu)5 Sn, ξ -(Au, Cu)5 Sn and δ -AuSn were formed and grew to form a full-compound joint after about 150 h aging. The second is the conversion of the full-compound joint. The IMCs converted to ξ ′ phase when the aging time extends to 250 h, and transformed to ε -(Au, Ni, Cu)Sn2 and η -(Au, Ni, Cu)Sn4 after 350 h aging. The thicker gold layer and thinner solder joint can promote the growth of the IMCs. ß -(Au, Ni, Cu)10 Sn emerged in Au/SnSb-CuNiAg/(Au)Ni in this research, which is not usually found. Originality/value: The results in this study have a significant meaning for the application of the new Sn-5Sb-1Cu-0.1Ni-0.1Ag in harsh conditions.